Tìm x bt::
6x+2.4=53:52+9
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
6x+2.4=5^3:5^2+9
6x+8=5+9
6x+8=14
6x=14-8
6x=6
x=6:6
x=1
(5^3 là 5 mũ 3,5^2 là 5 mũ 2)
Đặt \(S=7+7^2+7^3+...+7^{52}\)
\(\Rightarrow7S=7^2+7^3+7^4+...+7^{53}\)
\(\Rightarrow7S-S=6S=7^2+7^3+7^4+...+7^{53}-\left(7+7^2+7^3+...+7^{52}\right)\)
\(\Leftrightarrow6S=7^{53}-7\)
\(\Rightarrow S=\frac{7^{53}-7}{6}\)
Thay vào biểu thức ta có:
\(\frac{6x\left(7^{53}-7\right)}{6}+7=7^{53}.\)
\(\Leftrightarrow x\left(7^{53}-7\right)=7^{53}-7\)
\(\Rightarrow x=1\)
đặt A=\(7+7^2+...+7^{52}\)
7A =\(7^2+7^3+...+7^{53}\)
=>7A-A=\(\left(7^2+7^3+...+7^{53}\right)-\left(7+7^2+...+7^{52}\right)\)
6A=\(7^{53}+7\)
A=\(\frac{7^{53}+7}{6}\)
TA CÓ : 6X.\(\left(7+7^2+...+7^{52}\right)\)+7=\(7^{53}\)
(=)6X.\(\frac{7^{53}+7}{6}\)+7=\(7^{53}\)
(=)6X.\(\frac{7^{53}+7}{6}\)=\(7^{53}-7\)
(=)X.\(7.\left(7^{52}+1\right)\)=\(7.\left(7^{52}-1\right)\)
X=7.\(\left(7^{52}-1\right):[7.\left(7^{52}+1]\right)\)
X=\(\frac{7^{52}-1}{7^{52}+1}\)
`#3107`
`52(9 - x) = 52?`
`=> 9 - x = 52 \div 52`
`=> 9 - x = 1`
`=> x = 9 - 1`
`=> x = 8`
Vậy, `x = 8.`
a. ĐKXĐ: x \(\ne\pm3\)
b. M = \(\frac{3}{x-3}+\frac{6x}{x^2-9}+\frac{x}{x+3}\)
= \(\frac{3\left(x+3\right)}{\left(x-3\right)\left(x+3\right)}+\frac{6x}{\left(x-3\right)\left(x+3\right)}+\frac{x\left(x-3\right)}{\left(x-3\right)\left(x+3\right)}\)
= \(\frac{3x+9+6x+x^2-3x}{\left(x-3\right)\left(x+3\right)}\) = \(\frac{9+6x+x^2}{\left(x-3\right)\left(x+3\right)}\)= \(\frac{\left(x+3\right)^2}{\left(x-3\right)\left(x+3\right)}=\frac{x+3}{x-3}\)
c. M = 0 hay \(\frac{x+3}{x-3}=0\) => x + 3 = 0 <=> x = -3 (Loại)
\(6x+2.4=5^3:5^2+9\)
\(6x=5+9-8\)
\(6x=6\)
\(x=1\)
6x+2.4=5\(^3\):5\(^2\)+9
6x+8=5+9
6x+8=14
6x=14-8
6x=6
x=6:6
x=1